Growth And Food Habits Of Red Snapper (Lutjanus Malabaricus) Catched In The Waters Of Central Mamuju, Makassar Strait - Dananjaya, IWK Kantun; Ernawaty, Ernawaty; Cahyono, Indra (Fakultas Perikanan dan Ilmu Kelautan Universitas 17 Agustus 1945 Cirebon, 2024)
Red snapper is a basic fish that has economic value with intensive use and high market demand, so it is thought to have undergone biological changes. In this regard, the research aims to analyze the size distribution, growth and food habits of red snapper caught in Mamuju waters. This research is classified as a survey type with data sources from fishermen's catches. The results showed that the average size distribution of red snapper from Kambunong was ± 36.93 cm for males and ± 44.65 cm for females, Babana ± 29.81 cm for males and ± 41.14 cm for females, Pangale ± 31.45 cm for males and ± 33.75 cm female. The growth pattern of samples from Pangale and Kambunong was negative allometric, while Babana had a positive allometric pattern. The main types of food are white shrimp, tiger prawns, lencam fish, crab and lobster while cuttlefish is a complementary food. To catch red snapper, both males and females should use red snapper as their main food